2021
DOI: 10.3390/jpm11121360
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Protein Diet with a Renal-Specific Oral Nutrition Supplement Helps Maintain Nutritional Status in Patients with Advanced Chronic Kidney Disease

Abstract: A low-protein diet (LPD) is recommended to patients with non-dialysis advanced chronic kidney disease (CKD) for delaying renal function decline. However, this approach potentially prevents an adequate calorie and micronutrient intake. We examined the influence of an LPD including a renal-specific oral nutrition supplement (RONS) on the nutrition status of patients with stage 3b–5 CKD. This multicenter, open-label study prospectively enrolled patients over 18 years of age, with an estimated glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 22 The lack of clinically meaningful associations between biochemical parameters and symptom burden has been observed in previous studies of patients receiving dialysis, with negligible correlations between changes in biochemical markers and changes in ESASr:Renal. 19 However, composite nutrition scores, such as the Malnutrition Inflammation Score and Subjective Global Assessment, have demonstrated associations with quality-of-life domains in HD 23 - 25 and non-dialysis CKD. 26 …”
Section: Discussionmentioning
confidence: 99%
“… 22 The lack of clinically meaningful associations between biochemical parameters and symptom burden has been observed in previous studies of patients receiving dialysis, with negligible correlations between changes in biochemical markers and changes in ESASr:Renal. 19 However, composite nutrition scores, such as the Malnutrition Inflammation Score and Subjective Global Assessment, have demonstrated associations with quality-of-life domains in HD 23 - 25 and non-dialysis CKD. 26 …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review indicated that dialysis treatment involving a mix of various macronutrients for up to 12 months significantly increased lean body mass [ 28 ]. In a previous single-arm study, 35 patients with stage 3b-5 CKD adhering to a dietitian-guided LPD and a renal-specific formula noted considerable improvements in body weight and grip strength over six months [ 29 ]. In contrast with past studies, our findings showed that an LPD combined with a 6% LPF prompted a slight increase in body weight, muscle mass, and fat-free mass.…”
Section: Discussionmentioning
confidence: 99%
“…First, the current study may have been too short in its relative duration and could not improve nutritional status. Previous studies have reported that body weight and BMI using renal-specific ONSs for six months were enhanced in patients with advanced CKD [31]. The ability to significantly increase energy intake to the extent that anthropometric indicators are also improved may take time in patients with end-stage renal disease who are at risk of PEW.…”
Section: Discussionmentioning
confidence: 99%